2014
DOI: 10.1177/0194599814564366
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and Intraoperative Treatments Associated with Head and Neck Free Tissue Transfer Complications and Failures

Abstract: Objective To investigate the association between perioperative patient characteristics and treatment modalities (eg, vasopressor use and volume of fluid administration) with complications and failure rates in patients undergoing head and neck free tissue transfer (FTT). Study Design A retrospective review of medical records. Setting Perioperative hospitalization for head and neck FTT at 1 tertiary care medical center between January 1, 2009, and October 31, 2011. Subjects and Methods Consecutive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
32
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(37 citation statements)
references
References 36 publications
4
32
1
Order By: Relevance
“…Our group recently published a retrospective review undertaken in an attempt to determine risk factors associated with suboptimal outcomes after head and neck FTT . We found little evidence that further optimization could be accomplished without challenging the existing treatment paradigm, namely i.v.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our group recently published a retrospective review undertaken in an attempt to determine risk factors associated with suboptimal outcomes after head and neck FTT . We found little evidence that further optimization could be accomplished without challenging the existing treatment paradigm, namely i.v.…”
Section: Discussionmentioning
confidence: 99%
“…However, recent work has repeatedly shown an association between fluid overload and increased perioperative morbidity, leaving the anesthesia team with few evidence‐based options for blood pressure management in these operations . In addition, retrospective studies have shown that vasopressor use occurs at a high frequency (>50%) in FTT reconstruction cases, despite surgical policies discouraging their use …”
Section: Introductionmentioning
confidence: 99%
“…Various authors have attempted to quantify risk of flap failure preoperatively by using the American Society of Anesthesiologists (ASA) grade or Charlson Comorbidity Index (CCI) . And although coronary artery disease (CAD) has been tied to increased risk of flap failure in two independent studies, there is a lack of consensus on the impact this has on free flap success.…”
Section: Discussionmentioning
confidence: 99%
“…Venous congestion occurs more commonly due to slower flow, more compressible vessels, and lower pressure of blood flow compared to the artery. Flaps may become venously engorged secondary to a number of processes including problems with the pedicle and anastomosis, large flap size, poor perforators, excessive fluid administration, dependency, and lymphedema (Hand et al, ; Urken et al, ). Some cases of venous congestion have been successfully managed using adjuvant leech therapy (Whitaker et al, ).…”
Section: Introductionmentioning
confidence: 99%